Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 2711 và 848
2711 > 848
b) 6255 và 1257
6255 > 1257
c) 525 và 6*522
525 > 6*522
đ) 7*213 và 216
7*213 < 216
a, 920=(92)10=8110
vì 81 <9999 suy ra 920<999910
b, vì 3>2 suy ra 321>221
a) 3^40= 3^4.10=(3^4)10=81^10
11^21> 11^20=11^2.10=(11^2)10=121^10
→ 3^40< 11^21
b) 2^195=2^15.13=(2^15)13=32768^13
3^130=3^10.13= (3^10)13=59049^13
→2^195<3^130
c) 2^90=2^5.18=(2^5)18= 32^18
5^36=5^2.18=(5^2)18=25^18
→2^90>5^36
Trả lời:
\(x=\frac{9^{11}+2}{9^{11}+3}=\frac{9^{11}+3-1}{9^{11}+3}=\frac{9^{11}+3}{9^{11}+3}-\frac{1}{9^{11}+3}=1-\frac{1}{9^{11}+3}\)
\(y=\frac{9^{12}+2}{9^{12}+3}=\frac{9^{12}+3-1}{9^{12}+3}=\frac{9^{12}+3}{9^{12}+3}-\frac{1}{9^{12}+3}=1-\frac{1}{9^{12}+3}\)
Ta có: \(9^{11}< 9^{12}\)
\(\Leftrightarrow9^{11}+3< 9^{12}+3\)
\(\Leftrightarrow\frac{1}{9^{11}+3}>\frac{1}{9^{12}+3}\)
\(\Leftrightarrow-\frac{1}{9^{11}+3}< -\frac{1}{9^{12}+3}\)
\(\Leftrightarrow1-\frac{1}{9^{11}+3}< 1-\frac{1}{9^{12}+3}\)
\(\Leftrightarrow x< y\)
Vậy x < y
a) Ta có: (-32)9 = [(-2)5]9 = (-2)45 = (-2)13 . 232
(-18)13 = (-2 . 9)13 = (-2)13 . 913
Xét 232 và 326:
232 = (24)8 = (23 . 2)8 = (23)8 . 28 = 88 . (22)4 = 88 . 44
913 = 98 . 95
Vì 88 < 98 và 44 < 95
\(\Rightarrow\) 88 . 44 < 98 . 95
\(\Rightarrow\) (-2)13 . 232 > (-2)13 . 913
Vậy (-32)9 > (-18)13
b)Ta có:\(5^{21}< 5^{25}=5^{10}\cdot5^{15}< 6^{10}\cdot20^{10}=120^{10}< 124^{10}\)
\(\Rightarrow5^{21}< 124^{10}\)
Giải thích các bước giải:
Ta có:
\(84^{11}>81^{11}=\left(9^2\right)^{11}=9^{22}>9^{21}\)
=> \(-84^{11}< -9^{21}\)
\(\Leftrightarrow\left(-84\right)^{11}< \left(-9\right)^{21}\)
12345678